Students’ versus Teachers’ Attitudes and Perceptions towards World Englishes - 김현옥 (영어영문학연구, 2018)
The study investigates Korean EFL students’ and teachers’ attitudes towards World Englishes and perceptions regarding grammatical features found in World Englishes. For the purposes, a self-report questionnaire was completed by 62 college students and 41 secondary school English teachers in Korea. Four factors were extracted: (1) Preference of Learning Standard English; (2) Awareness of Different English Varieties; (3) Perception of Linguistic Features of World Englishes; and (4) Recognition of the Value of World Englishes. While both students and teachers endorsed the role of World Englishes in international communication, they still preferred having teachers who speak standard English. Whereas teachers were better aware of World Englishes and slightly more positive towards them, students were more concerned about the grammatical variations found in World Englishes. Although students’ academic years or teachers’ length of field experience did not significantly influence their attitudes, overseas experience was positively related to their awareness of World Englishes. Findings suggest that Korean ELT circles should have teachers and students better informed of the value and features of World Englishes to help them adequately prepared for authentic intercultural communication.
Keywords: 공용어로서의 영어; 표준어; 학생태도; 교사인식; 세계영어; English as a lingua franca (ELF); standard language; student attitudes; teacher perceptions; World Englishes